Ethhomathematics in the Design and Variety of Maimoon Palace Ornaments in Medan City - Nur Azizah Auliallah Li Muchand; Rusydi Ananda (Universitas Muhammadiyah Enrekang, 2022)
In general, the purpose of this research is from the philosophy contained in one of the tours in North Sumatra, precisely in the city of Medan which is often called the Maimoon Palace. So this research describes the activities related to ethnomathematics. This study found a relationship between Mathematics in the Form of Design and the Variety of Ornaments of the Maimoon Palace. This study uses objects from both namely: Points, Lines, Fields, Shapes and Spaces. The results of this study also have a basic concept that uses mathematical elements in geometry lessons contained in the design and ornaments of the Maimoon Palace. As for the Mathematical concepts, there is the development of basic ethnomathematical science to mathematics lessons in the special geometry field such as a). wake up flat, (b). build space, (c). The concept of lines, and other mathematical elements (flat sides, points, and angles). Based on this research, there are results from mathematical concepts related to the main object, namely design and ornamentation when visiting the tour. So there is a variety of cultures that are applied to mathematical concepts.